'Ministering Confusion': Rebellious Quaker Women (1650-1660)' - Gill, Catie (Quaker studies, 2004)
This paper assesses the position of women within the Quaker community, concentrating on their ministerial roles. Female prophets and preachers were visible during the first decade of Quakerism, and the early years prove fruitful for exploration of women's experiences. In order to consider the difficulties women faced when taking a public role in support of Quakerism, some context on seventeenth-century attitudes to women will be provided. It will be argued that women had to challenge patriarchal notions that the 'weaker' sex should be silent, passive and obedient. In contrast to prevailing seventeenth-century norms, the potential radicalism of the Quaker approach to gender can be demonstrated. Yet, the majority of this paper deals with evidence showing that women were chastised by other Quakers for apparently departing from the conventional female roles. Hence, this paper examines the co-existence of radical, egalitarian attitudes to gender alongside more conservative, and restrictive evaluations of women's ministry.